Autophagy pathways in drug abusers after forensic autopsy: LC3B, ph-mTOR and p70S6K analysis. (January 2019) - Chindemi, Chiara; Cirielli, Vito; Cima, Luca; Danzi, Olivia; Raniero, Dario; Tagliaro, Franco; Turrina, Stefania; Eccher, Albino; Ghimenton, Claudio; Bortolotti, Federica; Brunelli, Matteo; De Leo, Domenico
Abstract: Introduction: Autophagy plays a role in various central nervous system diseases. Little is known about its molecular activation in drug addiction. Our aim was to investigate the signalling pathways of autophagy in brain tissues from drug abusers. Methods: Twenty-five drug abusers with acute lethal intoxication and 10 controls were medico-legally autopsied. Brain-tissue samples from the parietal cortex and cerebellum were obtained. Expression of LC3B, phospho-mTOR (ph-mTOR) and phospho70S6 Kinase (p70S6K) was identified in tissue microarrays, with three tissue spots per case. Blood, urine or vitreous humour were tested in all cases to identify the acute intoxication. Hair analysis was performed in 14 cases to confirm chronic intoxication; the remaining cases had a documented medical history of chronic abuse. Results: The autophagy marker LC3B was always positive on both the cortex and the cerebellum, stratified as strongly in 18 (72%) cases and weakly positive in seven (28%) cases. ph-mTOR was negative in all cases. The p70S6K molecule showed positivity in 14 (56%) cases on cortex tissue. The cerebellum was always negative, except for Purkinje cells. Drug abusers had statistically more double positive cases (LC3B–p70S6K) than controls ( p =0.0094). Conclusion: Autophagy pathways were activated in our series, and 56% of drug abusers showed simultaneous LC3B–p70S6K immunoexpression on tissue from the parietal cortex and cerebellum. This may be of value in autopsy practice as an indicator of brain damage due to drug abuse and could serve as alternative or additional double sensitive diagnostic method to detect drug-related deaths using a tissue-based rationale.